Study on Companies Awareness Level In Life Insurance In India: A Study on Purchasing and Satisfaction Level of Health Insurance Policy in India (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Studies on purchasing andpreference on health insurance policy was carried on.  It clearly indicates the satisfaction levelof the respondents with regards to various services offered by health insuranceproviders. With terms and conditions of the policy 46.7 percent of the respondentsare neutral in their response, 36.3 percent are satisfied, 14.8 percent aredissatisfied and only 2.2 percent are highly satisfied. With premium schedule51.1 percent of the respondents are neutral, 24.4 percent are satisfied, 20.0percent are dissatisfied, 3.7 percent are highly satisfied and 0.7 percent arehighly dissatisfied. 45.2 percent are dissatisfied with premium in one lotfactor, 34.8 percent are neutral in their response, 9.6 percent are highlydissatisfied, 8.1 percent are satisfied and only 2.2 percent are highlysatisfied. 54.1 percent of the respondents are dissatisfied with thedistribution services whereas 20.7 percent are neutral and 25.2 percent arehighly dissatisfied. With promotional services, 60.0 percent are highlydissatisfied, 36.3 percent are dissatisfied and only 3.7 percent are neutral intheir response. 55.7 percent of the respondents are neutral in their responsewith regard to process of claim settlement, 24.6 percent are dissatisfied, 13.1percent are satisfied and 6.6 percent are highly dissatisfied.